Renoprotective effects of Caraway (Carum carvi L.) essential oil in streptozotocin induced diabetic rats - Neveen H. Abou El-Soud, Nabila A. El-Lithy, Gamila El-Saeed, Mohamed S. Wahby, Mona Y.Khalil, Fatma Morsy, Nermeen Shaffie (Journal of Applied Pharmaceutical Science, 2014)
Aim of the study was to assess the renoprotective effect of Carum carvi essential oil. Thirty male albino rats were divided into three groups: normal control (group A), diabetic positive control (group B), and experimental (group C) receiving Carum carvi oil as a renoprotective agent at 10 mg/kg of body weights orally. Group B and C rats received STZ (60 mg/kg) for induction of diabetes. Rats with fasting blood glucose levels over 200mg /dl were considered diabetic. Blood samples were collected on the 22 th day for the determination of glutathione peroxidase and glucose. Kidneys were also extracted for examination. Carum carvi oil was analysed using the GC and GC/MS analysis. The major components of caraway essential oil were Carvone (70.1%) followed by γ-Terpinene (12.6%) and Limonene (5.5%) in addition to some minor compounds including Linalool (0.7%), Thymol (0.5%), γ –Cadinene (0.5%), α- Farnesene (0.4%), δ- Cadinene (0.4%). The diabetic group rats showed an increase in the serum level of glucose, and decrease in glutathione peroxidase. 10 mg/kg body weight dose of Carum carvi oil significantly corrected these parameters.The morphological examination of group B rats kidneys showed glomerular and tubular degeneration with massive cellular infiltration, hemorrhage in interstitial tissue and deformed renal tissue architecture. Whereas the kidney rats in group C showed marked improvement with minor pathological changes. Conclusion: Carum carvi oil showed renoprotection against diabetic nephropathy. This could be contributed to Carum carvi constituents, especially carvone , γ –Terpinene and Limonene which have strong anti-oxidant activity.
Keywords: Carum carvi essential oil , diabetes , kidney , histological study.